Novel dengan Berbagai Konflik Tokoh Utama dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia di SMA - Nur Hikmah; Nini Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2023)
Conflict is an important part of the novel. The existence of conflict in a novel makes the story in the novel more alive. The conflict presented in the novel by the author cannot be separated from the fact that its existence is part of human life. The problem in this study is how the conflicts of the main character in the novel and its implications for Indonesian language learning. The problem is in line with the objectives in the study, namely to describe the conflicts experienced by the main character in the novel and its implications for Indonesian language learning. This type of research is a qualitative research using descriptive method with literary psychology approach. Based on the results the conflicts experienced by the main character in the novel are inner conflicts (indecision, sadness, anxiety), physical conflicts, and social conflicts (quarrels, sexual violence, oppression, accusations). However, the novel shows more social conflict than inner conflict or physical conflict.